Cognições sobre o passado: avaliação do pensamento contrafactual em grupos específicos - Justino, Florença Lucia Coelho (Universidade Federal de São Carlos, 2017)
Imagining and reasoning about hypothetical possibilities is an exclusively human characteristic and confers on cognition an important status for the study of different themes. The need for studies about imaginative processes is based on the inventive capacity of the human mind and on the flexibility that it must take in the face of the technological evolutions of today's world. Counterfactual thinking is a type of imaginative thinking characterized by mental simulation of alternatives to past events to alter the sequence of events to arrive at a different outcome from what actually occurred. Studies have indicated that this type of cognition is involved in different cognitive processes, such as decision making processes, moral judgments, motivations, inferences that enable behavioral changes and the adaptation of the individual and emotional elaborations. The studies on cognitions about past events in specific groups are necessary since they can give indications of the function that this type of thinking has for each group and also to focus on the different ways that the groups have in perceiving and to modify their thoughts in relation to the lived reality, as well as the consequences of thinking counterfactually to the emotions, cognitions and behaviors of each group from its specific characteristics. This doctoral thesis is organized in the form of three articles. The first one refers to the literature review of the area of counterfactual thinking that aimed to gather, evaluate and systematize the main findings of research on the subject between the years 2005 and 2015. The second article refers to the evaluation of counterfactual thinking in two specific groups: women victims of intrafamily violence and women with indicative of depression and analyzed the modifications from explicit request, called directed counterfactual thoughts. The third and last article deals with the evaluation of counterfactual thoughts elaborated spontaneously and under the choice of pre-defined alternatives.
Keywords: Pensamento contrafactual; Produção científica; Avaliação do pensamento contrafactual; Counterfactual thinking; Scientific production; Evaluation of counterfactual thinking; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA COGNITIVA